Decree of the Prime Minister No. 1657 of the year 2015 Issuing The Executive Regulations of the Mineral Resources law = قرار رئيس مجلس الوزراء رقم 1657 لسنة 2015 بإصدار اللائحة التنفيذية لقانون الثروة المعدنية / Prime Minister. - Egypt. Prime Minister. (2025)
1. Preliminary provisions -- 2. Rules related to mines -- 3. Rules of quarries -- 4.Rules of salt pans -- 5. General provisions.